Technology driven integration of occupational health services into primary healthcare settings - Kumar, M. Mohan; Ruikar, Manisha (International Journal Of Community Medicine And Public Health, 2020)
India, a growing economy has population exceeding 1.21 billion. Of this more than 65.5% people belong to the working age group. Total workers have doubled during 1981-2011, an increase in both organized and unorganized sectors. India contributes 1/5th of non-fatal injuries, half of fatal injuries, 1/5th of occupational diseases. Early identification and appropriate management of occupational morbidities is very much possible at primary healthcare settings. The deficit of Factory Medical Officers in India is approximately 60% and hence factory workers are likely to seek primary healthcare settings for their ill-health. But doctors are neither sensitized nor trained even to suspect occupation as a cause. Thus, integration of occupational health services into primary healthcare is the need of the hour. Technology may be adopted to train not only medical officers but nurses, auxiliary nurse midwives and other healthcare workers to identify and manage occupational health problems in a comprehensive manner.